Beyond Subsidized Credit: Sharia-Compliant Microfinance as a Catalyst for Inclusive MSME Growth - Berampu, Faiz Aqila Izura Atanta; Nurbaiti, Nurbaiti; Atika, Atika (International Ecsis Association, 2026)
This study investigates whether Sharia-compliant KUR (Credit program) distributed by Bank Syariah Indonesia (BSI) functions merely as subsidized financing or as a strategic instrument for inclusive and sustainable MSME growth. Despite the recognized importance of KUR in supporting small enterprises, limited research has examined its impact within a Sharia-compliant framework that integrates ethical finance principles with microenterprise growth. Addressing this gap, the study employs an explanatory sequential mixed-methods design combining quantitative analysis and qualitative interviews with MSME actors in Medan City. Quantitative findings reveal a significant positive effect of Sharia-compliant microfinance on MSME growth, particularly in terms of revenue growth, employment expansion, and business stability. MSMEs receiving Sharia-compliant microfinance demonstrate stronger performance and higher resilience compared to non-recipients. Qualitative insights further indicate that beyond financial capital, the program enhances entrepreneurial confidence, strategic planning capacity, and optimism in navigating post-pandemic economic challenges. The murabaha-based financing mechanism and ethical, interest-free structure contribute to increased trust and perceived fairness among beneficiaries. The study contributes to the microfinance dual mission debate by demonstrating that Sharia-compliant microfinance reconciles financial sustainability with social outreach. It extends microfinance theory beyond liquidity provision by integrating ethical finance principles with MSME growth dynamics. The findings suggest that Sharia-compliant microfinance can serve as a transformative development instrument, fostering inclusive growth, employment generation, and sustainable regional economic development.